Study of the causal relationship between gastroesophageal reflux disease and hypertension through two-sample Mendelian randomization analysis - Li, Weige; Wang, Qian; Li, Wenjie; Liu, Xiang; Li, Zuobin; Dai, Qi (Frontiers in Cardiovascular Medicine, 2024)
Objective: The purpose of this study was to investigate the causal relationship between gastroesophageal reflux disease (GERD) and hypertension using a two-sample Mendelian randomization analysis. Methods: The associated data of GERD with hypertension were derived from the genome-wide association study (GWAS) database, and two-sample Mendelian randomization (MR) analysis was performed using methods including inverse variance weighting (IVW), MR-Egger, and weighted median (WM) to investigate the causal association between GERD and hypertension. Results A total of 16 single nucleotide polymorphisms (SNPs) strongly associated with GERD were screened out, and the IVW suggested a causal relationship between GERD and hypertension (OR: 1.057; 95% CI: 1.044–1.071; P < 0.05). The weighted median also showed a similar relationship (OR: 1.051, 95% CI: 1.032–1.07; P < 0.05). In addition, no heterogeneity or horizontal pleiotropy was observed, suggesting a robustness of the outcome. Conclusion: There is a positive causal relationship between GERD and hypertension.